The silent strain: a systematic review and meta-analysis on the prevalence of occupational stress among Pakistani nurses - Reza Ghanei Gheshlagh; Madiha Mukhtar; Kainat Asmat; Simin Sharafi (BMC Nursing)
Abstract Background Occupational stress in the nursing profession is higher than in many other occupations, significantly impacting nurses’ physical and mental health, job satisfaction, and the quality of patient care. It often leads to burnout and the decision to leave the profession. Various studies conducted in Pakistan have reported different findings. Therefore, this systematic review and meta-analysis aimed to estimate the pooled prevalence of occupational stress among nurses in Pakistan. Methods Databases such as Scopus, Medline, Web of Science, EMBASE, and CINAHL were searched, including studies published from 2000 to September 2024. The screening process, article selection, data extraction, and quality assessment were all conducted independently by two authors. Any disagreements were resolved through consultation. Heterogeneity among studies was assessed using the I² statistic and Cochran’s Q test. Subgroup analysis based on the study location (city) was performed. The relationship between occupational stress prevalence and publication year and sample size was evaluated using meta-regression. Publication bias was assessed using funnel plots and the Egger test. All analyses were conducted using a random-effects model with Stata software version 17. Results Eleven studies with a sample size of 1636 participants were included. The prevalence of mild, moderate, and severe occupational stress was 16% (95% CI: 10–21), 48% (95% CI: 36–61), and 30% (95% CI: 20–41) respectively. The prevalence of mild occupational stress was highest in other cities, moderate stress was most common in Lahore, and severe stress was more prevalent in Karachi. No significant relationship was found between occupational stress prevalence and publication year or sample size. Publication bias for mild and severe occupational stress was significant, but the trim-and-fill analysis showed no impact on the results. Sensitivity analysis confirmed the stability of the findings. Conclusion This meta-analysis estimates the high prevalence of occupational stress among nurses in Pakistan, with moderate stress being most common. Differences in stress levels between cities may be influenced by local factors. Despite publication bias, the results remain stable and reliable, emphasizing the need for addressing occupational stress to enhance nurse well-being and patient care quality.